Trust and Complexity in Vertical Relationships - Giacomo Calzolari; Leonardo Felli; Johannes Koenen; Giancarlo Spagnolo; Konrad O. Stahl (CESifo GmbH, 2024)
We investigate the role of mutual trust in long-term vertical relationships involving trades of complex goods. High complexity is associated with high contract incompleteness and hence the increased relevance of trust-based relational contracts. Contrary to expectations, we find that changes in trust do not impact the quality of highly complex objects. Instead, higher trust improves the quality of less complex objects. Even more surprisingly, trust is associated with more competi-tion in procurement, again for low tech objects. This complexity-based difference persists even when the same supplier provides both types of objects, suggesting relational contracting may be object-specific. These findings are derived from a comprehensive survey of buyers and critical suppliers in the German automotive industry. We explain these results with a relational contracting model, where the cost of switching suppliers is technology-specific and increases with object complexity, shifting bargaining power and altering the effects of trust on each party's incentives.
Keywords: D86; L14; L62; O34; 330; relational contracts; complexity; bargaining power; trust; high-tech industries